Hubungan Jenis Kelamin, Usia, dan Urutan Kelahiran dengan Kemampuan Mengkombinasikan Warna Menggunakan Media Finger Painting - Nurafiffah Sekar Pamuji; Sodikin Sodikin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Cognitive development includes children's thinking abilities in processing learning outcomes. The ability to recognize colors is included in cognitive development. Combining color with coloring followed by children drawing using finger painting media is an activity that is not monotonous. In preschool children this activity can express their feelings, develop intellectual, physical, perception, creativity, aesthetic and social. This research aims to find out determine the relationship between children's characteristics and the ability to combine colors using the media of finger painting in PAUD Giri Saloka Karangendep.Methods: This research is a quantitative descriptive analytic study with a cross sectional approach. The sample of this study was preschool children with a total of 28 respondents using the total sampling method in February 2020. The research instrument used an observation sheet with the Chi-Square test.Results: Most respondents were female (71.4%), aged 6-7 years (75%) and the order of the first child (35.7%), second child (28.6%) and last child (35.7%). Gender (p = 0.034; value = 6.767; df = 2), age (p = 0.029; value = 7.111; df = 2), child order (p = 0.884; value = 1.167; df = 4) indicate that there is no significant relationship (p value> 0.05).Conclusion: It can be concluded that there is a significant relationship between sex and age with the ability to combine colors using finger painting media. Meanwhile, there is no significant relationship between the order and the ability to combine colors using finger painting media.